2023
DOI: 10.1158/2767-9764.crc-22-0397
|View full text |Cite
|
Sign up to set email alerts
|

Distinct IDH1/2-associated Methylation Profile and Enrichment ofTP53andTERTMutations Distinguish Dedifferentiated Chondrosarcoma from Conventional Chondrosarcoma

Abstract: Dedifferentiated chondrosarcoma (DDCS) is a rare high-grade chondrosarcoma characterized by a well-differentiated chondrosarcoma (WDCS) component that abruptly transitions to a high-grade, non-cartilaginous sarcomatous component. To date, the molecular pathogenesis of DDCS and its distinction from conventional chondrosarcoma remain poorly understood. By targeted sequencing, we examined the mutational and copy number profiles of 18 DDCS, including macrodissected WDCS components, compared to 55 clinically sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Considering the genes of the E1/E2 signatures, we can hypothesize that the inhibitor produces a negative regulation of those genes linked to the cell cycle, proliferation and division, which would explain the general repression of E2F-controlled targets in T-CDS17#1 cells. Relevant to this finding, a recent study found that mutant IDH -induced methylation profiles in dedifferentiated chondrosarcomas were associated with upregulated expression of genes involved in G2/M checkpoints and E2F targets 57 . Among the E2F targets that we found repressed by enasidenib there are key mediators of progression through the G2/M phase of the cell cycle such as CDK1 , AURKA , PLK1 , WEE1 or CHK1 , while the expression of other inhibitors of proliferation such as TP53 , CDKN2A or CDKN1B increases after treatment with the inhibitor.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Considering the genes of the E1/E2 signatures, we can hypothesize that the inhibitor produces a negative regulation of those genes linked to the cell cycle, proliferation and division, which would explain the general repression of E2F-controlled targets in T-CDS17#1 cells. Relevant to this finding, a recent study found that mutant IDH -induced methylation profiles in dedifferentiated chondrosarcomas were associated with upregulated expression of genes involved in G2/M checkpoints and E2F targets 57 . Among the E2F targets that we found repressed by enasidenib there are key mediators of progression through the G2/M phase of the cell cycle such as CDK1 , AURKA , PLK1 , WEE1 or CHK1 , while the expression of other inhibitors of proliferation such as TP53 , CDKN2A or CDKN1B increases after treatment with the inhibitor.…”
Section: Discussionmentioning
confidence: 75%
“…In line with these non-canonical cases, we have not found changes in the methylation levels of the CDS17 chondrosarcoma models after treatment with enasidenib. The relevance of IDH mutant-induced epigenetic changes in chondrosarcoma has been revealed in previous studies showing a global hypermethylated status of IDH mutant cases 53, 57 . Although there could be technical biases arising from the comparison of epigenetic features in tissue samples and cultured cell lines, our methylome analysis of normal cartilage samples and chondrosarcoma cell lines also showed a high rate of hypermethylated genes in IDH2 mutated cells.…”
Section: Discussionmentioning
confidence: 85%
“…Although not associated with progression‐free or overall survival, the presence of TERT promoter mutations is hypothesized to be crucial for telomere maintenance during early stages of tumorigenesis. In dedifferentiated chondrosarcoma, by comparing microdissected well‐differentiated and dedifferentiated chondrosarcomatous components to conventional chondrosarcomas, a recent genomic profile showed that TERT promoter mutations were an early event in dedifferentiated chondrosarcoma [72].…”
Section: Clinically Significant and Recurrent Secondary Genetic Alter...mentioning
confidence: 99%
“…Introduction of mutant IDH generated USARCs in vivo [102]. Interestingly, global hypermethylation is reduced/reversed in dedifferentiated chondrosarcoma [72]. Further, downregulation of miR‐22, a downstream negative regulator of TET1, has been reported in both USARC and osteosarcoma, with a strong association with poor disease‐free survival [26,103].…”
Section: Clinically Significant and Recurrent Secondary Genetic Alter...mentioning
confidence: 99%
“…Genomic examination identified an overrepresentation of TP53, TERT promoter, and CDKN2A/B alterations in DDCS but copy-number alterations in DDCS was significantly lower. Integrating methylation and gene expression analysis revealed that distinctive methylation and transcriptional profiles related to IDH1/IDH2 were early events in DDCS [80,81]. SRY-box transcription factor 9 (SOX-9) is the master regulator of chondrogenesis and increases in chondrosarcoma tissue and is directly targeted by miR-145 [82].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%